Functionalisation of Electrospun Cellulose Acetate Membranes with PEDOT and PPy for Electronic Controlled Drug Release - Lago, Beatriz (2023)
Funding Information: This work was also supported by ERC-CoG-2014, CapTherPV, 647596. Publisher Copyright: © 2023 by the authors.